2021
DOI: 10.3390/antibiotics10111352
|View full text |Cite
|
Sign up to set email alerts
|

How Adding Chlorhexidine or Metallic Nanoparticles Affects the Antimicrobial Performance of Calcium Hydroxide Paste as an Intracanal Medication: An In Vitro Study

Abstract: The aim of our study was to explore the potential value of metallic (Ag, Cu, and Zn) salts, polymer/metallic nanoparticles, and chlorhexidine (CHX) for improving the antimicrobial activity of calcium hydroxide (CH) against E. faecalis and C. albicans, associated with persistent endodontic infections. A first screening was performed by determining minimum inhibitory/bactericidal concentrations (MIC/MBC). Antimicrobial activity of the CH paste mixed with metallic salts, chitosan or cyclodextrin polymer metallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
2
5
0
Order By: Relevance
“…In this study, a dose-dependent potentiation of the antimicrobial action of CH on P. gingivalis is observed, which is found in both the root canal and the periodontal pocket and is not susceptible to CH alone. In a previous publication, our group reported similar results with E. faecalis [ 28 ]. The dosage used in the bacterial culture medium in contact with the ICMs confirmed that CHX is released at a concentration of 2.25 mg/L after 24 h, which is close to the MICs of these bacteria [ 28 ].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In this study, a dose-dependent potentiation of the antimicrobial action of CH on P. gingivalis is observed, which is found in both the root canal and the periodontal pocket and is not susceptible to CH alone. In a previous publication, our group reported similar results with E. faecalis [ 28 ]. The dosage used in the bacterial culture medium in contact with the ICMs confirmed that CHX is released at a concentration of 2.25 mg/L after 24 h, which is close to the MICs of these bacteria [ 28 ].…”
Section: Discussionsupporting
confidence: 79%
“…In a previous publication, our group reported similar results with E. faecalis [ 28 ]. The dosage used in the bacterial culture medium in contact with the ICMs confirmed that CHX is released at a concentration of 2.25 mg/L after 24 h, which is close to the MICs of these bacteria [ 28 ]. CH and two combinations of CH + CHX were both effective in inhibiting biofilm formation and eradicating mature biofilms.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Another effective antimicrobial agent as an intracanal medication is the use of nanoparticles, including metal, polymeric and ceramic nanoparticles. These nanoparticles are commonly mixed in the calcium hydroxide paste as additives to enhance the antimicrobial potency of calcium hydroxide (Sy Agossa et al, 2021). One of the most studied metal nanoparticles against E. faecalis is silver nanoparticle (AgNP) due to its broad‐spectrum antimicrobial activity and simple fabrication procedures (Afkhami et al, 2015; Halkai et al, 2018; Noronha et al, 2017; Wu et al, 2014; Zheng et al, 2018).…”
Section: Future Directions: Nanoparticles and Antimicrobial Peptidesmentioning
confidence: 99%